alpha-Naphthoflavone acts as activator and reversible or irreversible inhibitor of rabbit microsomal CYP3A6 - Boek-Dohalská, L; Hodek, P; Sulc, M; Stiborová, M (Chemico-biological interactions, 2001)
This report describes the effect of alpha-naphthoflavone (alpha-NF), a known substrate, inhibitor and activator of several cytochromes P450 (CYP), on rabbit CYP3A6. Hepatic microsomes of rabbit pretreated with rifampicine (RIF), enriched with CYP3A6, as well as purified CYP3A6 reconstituted with isolated NADPH:CYP reductase were used as enzymatic systems in this study. The data from difference spectroscopy experiments showed that alpha-NF does yield a type I binding spectrum. This compound is oxidized by microsomal CYP3A6 into two metabolites (5,6-epoxide and trans-7,8-dihydrodiol). While alpha-NF is a substrate of CYP3A6, it also acts as an enzyme modulator. Under the conditions used, stimulation of 17beta-estradiol 2-hydroxylation by alpha-NF was observed. In contrast, this compound reversibly inhibited N-demethylation of erythromycin and tamoxifen, competitively with respect to these substrates, having the K(i) values of 51.5 and 18.0 microM, respectively. Moreover, alpha-NF was found to be an effective inactivator of progesterone and testosterone 6beta-hydroxylation catalyzed by CYP3A6 in RIF-microsomes. In addition, time- and concentration-dependent inactivation of human CYP3A4-mediated 6beta-hydroxylation of testosterone by alpha-NF, was determined. The inactivation of CYP3A6 followed pseudo-first-order kinetics and was dependent on both NADPH and alpha-NF. The concentrations required for half-maximal inactivation (K(i)) were 80.1 and 108.5 microM and the times required for half of the enzyme to be inactivated were 10.0 and 11.9 min for 6beta-hydroxylation of progesterone and testosterone, respectively. The loss of the enzyme activity was not recovered following dialysis, while 90% of the ability to form a reduced CO complex remained. This indicates the binding of alpha-NF to a CYP apoprotein molecule rather than to a heme moiety. Protection from inactivation was seen in the presence of all tested CYP3A substrates. Progesterone and testosterone protected CYP3A6 against inactivation competitively with respect to inactivator, erythromycin non-competitively and 17beta-estradiol showed a mixed type of protection. Here, we described for the first time that alpha-NF is capable of irreversible inhibition of microsomal rabbit CYP3A6 and human CYP3A4. The obtained results strongly suggest that the CYP3A active center contains at least two and probably three distinct binding sites for substrates.
Keywords: Microsomes, Liver; Recombinant Proteins; benzoflavony; Male; tamoxifen; Enzyme Activation; Hydroxylation; Erythromycin; hydroxylace; vysokoúčinná kapalinová chromatografie; inhibitory cytochromu P450; Methylation; metylace; vztah mezi dávkou a účinkem léčiva; Cytochrome P-450 Enzyme Inhibitors; mužské pohlaví; Enzyme Inhibitors; Benzoflavones; králíci; Chromatography, High Pressure Liquid; rekombinantní proteiny; Estradiol; Animals; Tamoxifen; aromatické hydroxylasy; Aryl Hydrocarbon Hydroxylases; zvířata; erythromycin; Rabbits; aktivace enzymů; Dose-Response Relationship, Drug; inhibitory enzymů; jaterní mikrozomy; estradiol